THE ANALYSIS OF PROBLEM BASED LEARNING IN LEARNING MATHEMATICS SENIOR HIGH SCHOOL - Tiara Anggraeni; Akhsanul In'am; Marhan Taufik (MEJ (Mathematics Education Journal), 2017)
This study aims to determine the level of response, the level of motivation,student learning outcomes and learning process using Problem Based Learningon learning mathematics. This research is descriptive research where there isno manipulation only to describe and to analyze the data obtained. Thisresearch uses quantitative research methods with the subjects of the studywhich amounted to 33 people. Data collection techniques used includequestionnaires, observations, interviews and tests. Data analysis used in thisresearch is qualitative analysis technique and quantitative analysis. The resultof the research indicates that the students response level to Problem BasedLearning is high with the percentage of achievement of 72.02% and thestudents' motivation level with the percentage of achievement of 70.05%.Student learning outcomes obtained using Problem Based Learning are quitesatisfactory. With the percentage of achievement level reached 75.75%. Withthe Minimum Exhaustiveness Criteria (KKM) score at the school is 75, so thatall students meet the given KKM.